Life-threatening autoimmune warm hemolytic anemia following treatment for multiple sclerosis with alemtuzumab. (May 2018) - Meunier, Benoit; Rico, Audrey; Seguier, Julie; Boutiere, Clemence; Ebbo, Mikael; Harle, Jean Robert; Schleinitz, Nicolas; Pelletier, Jean
Background: Alemtuzumab is a humanized monoclonal antibody directed at CD52 approved as a disease-modifying therapy for relapsing forms of multiple sclerosis (MS). Objective: To describe a case of a life-threatening autoimmune anemia occurring after a first course of alemtuzumab for relapsing-remitting MS in a 28-year-old male. Methods: Case report. Results: A 28-year-old male developed a life-threatening autoimmune anemia occurring 11 months after first alemtuzumab course. Conclusion: We report the third case of autoimmune hemolytic anemia following treatment with alemtuzumab in a young MS patient. Due to the severity of this adverse event, neurologists using this treatment should be alert.